Dyke-Davidoff-Masson Syndrome with crossed cerebellar atrophy - Kumar, Rohit; Kumar, Deepak; Mishra, Himanshu; Suman, Sanjay Kumar; Prasad, Umakant (Nepal Journal of Neuroscience, 2021)
Dyke-Davidoff-Masson Syndrome (DDMS) is a rare neurological condition characterised clinically by recurrent seizures, facial asymmetry, hemiplegia and mental retardation likely due to foetal or early childhood cerebral insult. We describe the MRI findings of DDMS in a 10-year-old male child. MRI brain revealed right cerebral atrophy, ipsilateral thickening of calvarium, right lateral ventricular dilatation, hyper-pneumatisation of frontal sinus, and contralateral cerebellar atrophy which are consistent with DDMS.